Payment and settlement system in Saudi Arabia: A multidimensional study - Anis Ali; Anas A. Salameh (Banks and Bank Systems, 2023)
A country’s payment and settlement system refers to payment means or instruments, procedures, supportive and technical services of clearance, fund transfer, and final settlement. To study the various dimensions of the payment and settlement system, an online survey was administered and 240 responses were collected from Saudi and non-Saudi nationals, while secondary data were obtained from the SAMA (Saudi Arabian Monetary Authority) website. Index numbers, percentages, ranks, Average Trend Growth Rate, and payment weights means are applied to get the mutual growth trend, average growth, and contribution of specific means in payment and settlement in Saudi Arabia. There are negative trends in the traditional payment and settlement system in Saudi Arabia. Based on the value (amount) of transactions, Mada (Debit card) and E-payment (SADAD – a payment system, and SARIE – Saudi Arabian Riyal Interbank Express) are the most significant contributors to online payment (51.63%), while POS (point of sale) is the fastest-growing (158%) means of payment and settlement in Saudi Arabia. The means of traditional payment and settlement negligibly (< 1%) contribute to the payment and settlement system in Saudi Arabia. The analysis of responses reveals that payment and settlement users were unsatisfied with the various dimensions of security (39%) and traceability (35%) of the payment and settlement systems in Saudi Arabia. All dimensions of security and traceability must be considered to increase the degree of satisfaction with payments and, in particular, settlements in Saudi Arabia. Acknowledgment The authors are grateful to the Deanship of Scientific Research, Prince Sattam Bin Abdulaziz University, Alkharj, Saudi Arabia, for providing funding to complete this project (Project No. 2021/02/18709).